Sistem Pendukung Keputusan Penentuan Pelanggan Terbaik Dengan Metode Simple Multi Attribute Rating Technique (SMART) - Rosalina, Vidila; Agustiawan, Wahyu; Purnamasari, Ayu (Jejaring Penelitian dan Pengabdian Masyarakat, 2023)
Jaya Bila Makmur is a nine-ingredient grocery store with products sold including cooking oil, instant noodles, rice, margarine, sugar, salt, and so on. With the continuous increase in the number of similar grocery stores on the market, business owners must have a strategy so that customers remain loyal and don't move elsewhere. One of the strategies is to give rewards or gifts to loyal customers for their cooperation so far, but the decisions taken by business owners are still not quite right. Then a decision support system (DSS) is needed that is able to provide alternative solutions. This system was built using PHP and MySQL, modeled using UML, and tested with Blackbox Testing. The method used in DSS uses the Simple Multi-Attribute Rating Technique (SMART) for multi-criteria decision making. The findings of this study are intended to assist in identifying the best customers who shop frequently and will become repeat customers. By implementing this decision-support system, business owners can improve their competitiveness and competence in the business world. From the results of the application built, it is hoped that it will make it easier for users to choose and determine the best customers according to the specified criteria.